Aggressive localized juvenile spongiotic gingival hyperplasia (LJSGS) in a 33-year-old patient: a case report - Vendruscolo, Joana Leticia; Gonçalves, Kariana Wan-Dall; Schussel, Juliana Lucena; Sassi, Laurindo Moacir (Journal of Oral Diagnosis, 2023)
The aim of this study is to report a case of an extensive and aggressive gingival lesion, compatible with localized juvenile spongiotic gingival hyperplasia (LJSGH), demonstrating the difficulties of diagnosis and management. A 33 years-old male patient was referred to Department of Oral and Maxillofacial Surgery at the Erasto Gaertner Hospital with a lesion on anterior maxillary gingiva, with 3-months evolution period. The patient had complete permanent dentition and good oral hygiene. The gingival hyperplasia involved the gums of teeth 11 and 12, and was solitary, asymptomatic, red, flaccid and bleeding on palpation. No palpable lymph nodes were found. An incisional biopsy was performed, with anatomopathological result of “squamous mucosa with pseudoepitheliomatous hyperplasia and lymphoplasmocytic infiltrate with neutrophils”. The lesion was fully excised and the anatomopathological report confirmed the biopsy showing no malignancy in the sample and negative for the investigation of fungus. Biofilm control, mouth rinses with hydrogen peroxide, Chlorhexidine Digluconate 0.12% and Amoxicilin 500mg+Potassium Clavulanate 125mg have not demonstrated efficacy, and the patient kept showing recurrence of the lesion in short time even after the complete excision. Against this situation, the patient was referred to an infectologist, by the suspicion of a resistant microorganism. He started antibacterial therapy with Sulfamethoxazole 800mg+Trimethoprim 160mg that showed good results after 3 months. Currently, the patient remains in follow-up without signs of recurrence. LJSGH is a clinicopathological benign entity that appears in young patients as a soft, bleeding and reddish mass, mainly in the buccal gingiva of the upper anterior maxilla and lonely in most cases. The management of this condition is very difficult because of the few cases described in literature, and establishing the correct diagnosis is essential to ensure that the appropriate treatment is followed.